Regulating employee representation in Postsocialist supervisory boards - Vliegenthart, Arjan (Amsterdam, 2006)
"This study explores the position of (organised) labour in the post-socialist corporate governance systems of Central Europe. The literature on post-socialist capitalism is rather united in its observation that organised labour is amongst the losers of the economic restructuring process. Yet, the explanations for this are different. Some scholars relate the weakened position of workers to domestic developments, whereas others have focused on the role of the European Union in the emergence of postsocialist industrial relations. A third group has related the weak position of labour to the position of Central Europe in the world economy. This study sets out to weigh these different accounts by looking at specific developments in one area; the regulation of employees in the corporation's Supervisory Board, which constitutes one of the primary elements of labour involvement in any corporate governance system. It focuses on the Hungarian case and looks at regulatory developments with regard to the position of employees in Supervisory Boards since the early 1990s."